2009
DOI: 10.1590/1809-9823.2009120110
|View full text |Cite
|
Sign up to set email alerts
|

Influência da tecnologia assistiva no desempenho funcional e na qualidade de vida de idosos comunitários frágeis: uma revisão bibliográfica

Abstract: sent them by mail or e-mail. It was observed a decrease of those elderly people's dependence while taking care of themselves, improvement of their socialization, betterment of caregivers' safety and peacefulness regarding the performance of functional activities by elderly people, and a lowering of constant frail aging people's hospitalizations and concomitant health-related costs. The conclusion was that assistive technology devices are quite valuable to community-dwelling frail elderly people, improving thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
(21 reference statements)
1
9
0
11
Order By: Relevance
“…when asked about the implementation of the AT in the daily routine, the resources most frequently cited by participants were the aid for daily life and practical life, architectural projects for accessibility and mobility aid. These results are similar to those found by Andrade and Pereira [7], which found, in most cases, that the use of AT by the elderly is related to the development of functional activities of daily living, intended to increase the independence, autonomy and level of safety, and reduce costs with possible fall-related hospitalizations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…when asked about the implementation of the AT in the daily routine, the resources most frequently cited by participants were the aid for daily life and practical life, architectural projects for accessibility and mobility aid. These results are similar to those found by Andrade and Pereira [7], which found, in most cases, that the use of AT by the elderly is related to the development of functional activities of daily living, intended to increase the independence, autonomy and level of safety, and reduce costs with possible fall-related hospitalizations.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the professionals working with the elderly, studies in Brazil, primary health care, show a superficial knowledge of the AT and indications for the elderly are still limited [7].…”
Section: Introductionmentioning
confidence: 99%
“…As pessoas com deficiência comumente apresentam dificuldades e precisam de auxílio para conseguir realizar atividades funcionais no seu dia a dia (OLIVEIRA; GAROTTI; SÁ, 2008;BERQUÓ, 2008;ANDRADE;PEREIRA, 2009;CRUZ, 2012). Para ajudá-las a ter melhor desempenho e satisfação em suas atividades, podem ser utilizados dispositivos de tecnologia assistiva (DTAs), definidos no Assistive Technology Act of 1998(UNITES STATES, 1998 qualquer item, parte de um equipamento ou sistema de produto, adquirido comercialmente, modificado ou personalizado, que é usado para aumentar, manter ou melhorar as capacidades funcionais das pessoas com deficiência".…”
unclassified
“…The combination of these factors demonstrated that the sample population of this study included individuals with high potential of frailty. Although there is no consensus in the literature regarding the definition of frailty, 2,8,[23][24][25] some evidences suggest that non-intentional weight loss, muscle strength decrease, fatigue, physical activity reduction, gait speed reduction, immobility due to fractures after accidental falls (especially of ilium and femur), chronic diseases, and polypharmacy are all markers of frailty syndrome in elderly individuals. 5,7,26,27 Regarding the performance of the tests applied along this study, the TUG execution time, which was superior to 10 seconds, identified that the elderly subjects may begin to have balance problems, once independent subjects, without balance problems complete the TUG in less than 10 seconds.…”
Section: 22mentioning
confidence: 99%